2019
DOI: 10.3174/ajnr.a5974
|View full text |Cite
|
Sign up to set email alerts
|

CT Texture Analysis of Cervical Lymph Nodes on Contrast-Enhanced [18F] FDG-PET/CT Images to Differentiate Nodal Metastases from Reactive Lymphadenopathy in HIV-Positive Patients with Head and Neck Squamous Cell Carcinoma

Abstract: BACKGROUND AND PURPOSE: Differentiating nodal metastases from reactive adenopathy in HIV-infected patients with [ 18 F] FDG-PET/CT can be challenging because lymph nodes in HIV-positive patients often show increased [ 18 F] FDG uptake. The purpose of this study was to assess CT textural analysis characteristics of HIV-positive and HIV-negative lymph nodes on [ 18 F] FDG-PET/CT to differentiate nodal metastases from disease-specific nodal reactivity. MATERIALS AND METHODS: Nine HIV-positive patients with head a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 33 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…So far, there have been few investigations performing texture or radiomic analysis of lymph nodes, especially in the neck. In a recent study performed on [18F]-FDG-PET scans that included a contrast-enhanced CT, it was reported that there are statistically significant differences between texture features of benign HIV-related lymphadenopathy compared to metastatic HNSCC nodes [48]. Another recent study reported that texture features of the primary HNSCC tumor may be useful for predicting associated cervical lymphadenopathy [49].…”
Section: Discussionmentioning
confidence: 99%
“…So far, there have been few investigations performing texture or radiomic analysis of lymph nodes, especially in the neck. In a recent study performed on [18F]-FDG-PET scans that included a contrast-enhanced CT, it was reported that there are statistically significant differences between texture features of benign HIV-related lymphadenopathy compared to metastatic HNSCC nodes [48]. Another recent study reported that texture features of the primary HNSCC tumor may be useful for predicting associated cervical lymphadenopathy [49].…”
Section: Discussionmentioning
confidence: 99%
“…Bianconi et al found that significant associations emerged between PET features, CT features, and histological type in Non small cell lung cancer (NSCLC) [20]. Kuno et al found that CT texture analysis may be a noninvasive method of obtaining additional quantitative information to differentiate nodal metastases from disease-specific nodal reactivity in HIV-positive patients with head and neck squamous cell carcinoma [21]. According to Li et al The newly developed 18F-FDG PET/CT radiomics signature was an independent biomarker for the estimation of micro-vascular invasion (MVI) and Disease Free Survival (DFS) in patients with very-early and early-stage HCC [22].…”
Section: Discussionmentioning
confidence: 99%
“…It is a method in which the shading of pixels in the region of interest is numerically measured, and parameters of "non-uniformity" such as uniformity, directionality, and contrast change are calculated. In recent years, texture analysis has been studied to predict outcomes and survival of patients with head and neck cancer, colorectal cancer, lung cancer, oesophageal cancer, and glioblastoma [10][11][12][13][14] as well as to differentiate between benign and malignant maxillary sinus masses, cervical lymph nodes, lung nodules, liver masses, adrenal nodules, and renal masses [15][16][17][18][19][20]. In the current study, there were significant differences in 8 of the 40 texture parameters between CNM-HPV-OPC and 2 nd BC.…”
Section: Discussionmentioning
confidence: 99%